أثر التدريس باستخدام التطبيقات التعليمية للحاسوب اللوحي في التحصيل لدى طلاب الصف السابع الأساسي في الرياضيات بإمارة أبو ظبي - الزعابى، محمد خلفان (الجامعة الأردنية - عمادة البحث العلمي, 2019)
This study aimed at investigating the effect of teaching using educational Applications of the tablet PC on the achievement of the seventh grade students in mathematics in Abu Dhabi. The sample of the study consisted of 109 male students who were intentionally selected. It was divided randomly into two groups, an experimental goup (54 students) who were taugh using tablet applications and a control group (55 students) who were taugh by the traditional strategies. An achievement test was prepared as a tool to collect he data and its reliability and validity were obtained. The results of the study revealed that there were statistical significant differences of the students' achievement on the levels of the test with regards to knowledge, comprehension, application and higher thinking skills due to the teaching method in favor of experimental group. Also, the study concluded some recommendations suggesting creative solutions to promote the educational process through integrating the Tablet PC educational applications to be the core of the educational process.
هدفت هذه الدراسة إلى معرفة أثر التدريس بواسطة استخدام الحاسوب اللوحي وتطبيقاته التعليمية في التحصيل الدراسي لطلاب الصف السابع الأساسي في مادة الرياضيات، في إمارة أبو ظبي بدولة الإمارات العربية المتحدة. تكونت عينة الدراسة من (109) طالب، تم اختيارهم بطريقة قصدية، ووزعوا عشوائية إلى مجموعتين: تجريبية وعدد أفرادها (54) طالبًا، درسوا باستخدام التطبيقات التعليمية للحاسوب اللوحی، وضابطة وعدد أفرادها (55) طالبًا درسوا باستخدام الطريقة الإعتيادية. وتكونت أدوات الدراسة من اختبار تحصیلي تم التأكد من صدقه وثباته أظهرت نتائج الدراسة وجود فروق دالة إحصائيًا في التحصيل الدراسي لدى الطلاب في مستويات الاختبار (التذكر، والفهم والاستيعاب، والتطبيق، ومهارات التفكير العليا)، تعزي لطريقة التدريس باستخدام الحاسوب اللوحي، لصالح المجموعة التجريبية، وقد أوصت الدراسة بمجموعة من التوصيات أهمها: وضع الحلول المبتكرة لنقل العملية التعليمية نقلة نوعية وذلك بالمبادرة إلى دمج الحاسوب اللوحي والتطبيقات التعليمية في عملية التعلم وجعلهما محورًا لعملية للتدريس.
Keywords: التطبيقات التعليمية -- الحاسوب اللوحي -- التحصيل الدراسى -- تدريس الرياضيات -- الصف السابع الأساسي -- إمارة أبو ظبي